Edge Effects of Truncated Dirac Solitons in Binary Waveguide Arrays - Truong, Tran Xuan; Hue, Nguyen Minh; Hoat, Phung Dinh (Communications in Physics, 2017)
We investigate the edge eﬀects of the optical analogue of the quantum relativistic Dirac solitons in binary waveguide arrays with Kerr nonlinearity when one tail of the Dirac soliton is truncated. We show that if the outermost waveguide of the binary waveguide array hosts the intense component of the truncated Dirac soliton, then Dirac soliton will be repeatedly bent towards the binary waveguide array edge. In the contrast, if the outermost waveguide of the binary waveguide array hosts the weak component of the truncated Dirac soliton, then Dirac soliton will be pushed away from the binary waveguide array edge. To the best of our knowledge, these unique features have not been found in any other systems.